LITHOSPHERE - IONOSPHERE RELATION AND ITS MODELING - Gokhberg M.B.; Shalimov S.L. (My University, 2000)
Offered in this paper is the critical analysis of the modern experimental results and theoretical views for the mechanisms of the lithosphere-ionosphere connection, cased by seismic activity at the final stage of earthquake preparation. The ionospheric disturbances, which take place above seismically active regions, manifest themselves as specific heterogeneities a few days before the earthquakes. These heterogeneities seem to be caused by the transmission of atmospheric gravitational waves across the ionosphere. These waves seem to be generated in seismically active regions by the flow of lithospheric gasses to the near-Earth atmosphere. The commercial earth-surface and subsurface nuclear explosions can be treated as model sources which can be responsible for similar processes in the ionosphere.